Forest Resources Management in Indonesia (1968-2004) A Political Ecology Approach - Hidayat, Herman (Springer Nature Singapore : Imprint: Springer, 2016)
This book explores the forestry sector and its context, investigating the management of forest resources in Indonesia. It covers topics including forest fires, deforestation, water pollution, depletion of biodiversity, climate change and environmental damages. The book adopts a political economy approach, elaborating on the role of direct actors such as the central government, private companies and local governments, and the role of indirect actors. In addition, readers will discover anthropological and sociological perspectives through engagement with local communities such as the Kutai, Banjar and Rejang ethnic groups, Chinese trading communities, NGOs and Academics.   Featuring interviews with 91 informants and participatory observations, the text draws on secondary literature to provide a comprehensive overview of the subject. This work is illustrated with figures, tables and maps and will be of particular interest to students and researchers of forest policies. It makes a valuable contribution to forest sciences and will also be useful to those in non-government organizations, politicians and business men with an interest in forest resources management, or a deeper interest in Indonesia.